Problems in the current psychiatry residency training program in Croatia: residents’ perspective - Rojnić-Kuzman, Martina (Array, 2009)
Abstract: The aim of this study is to evaluate the quality of the current residency training in psychiatry in Croatia using parameters of professional achievements of residents and their subjective evaluations of the residency training that is being offered. 66 residents from 15 Croatian psychiatric hospitals, clinics and wards in general hospitals fulfilled the questionnaire constructed to obtain information about the profile of psychiatry residents in Croatia, parameters of educational quality and evaluation of offered residency training as seen by residents. We interviewed 89% of all residents that had a trainee status in September and October 2006 in Croatia (66 out of 74). Study results indicate that Croatian psychiatry residents are derived from a pool of very good medical students and the majority is engaged in postgraduate studies and research activities and shows high interest in specific psychiatric fields such as psychotherapy and clinical psychiatry. Most of participants are only partially satisfied with the residency training that is being offered and feel that most problems reside from the lack of practical psychotherapy, the inefficiency of the mentorship system and the lack of funding resources. The results of this study revealed the major problems of psychiatry residents in Croatia. Following those results, we will perform the study that would include mentors and supervisors from different Croatian psychiatric centers. That could enable the development of specific interventions with aim to improve current residency training in Croatia